A Lack of Correlation between Brain-Derived Neurotrophic Factor Serum Level and Verbal Memory Performance in Healthy Polish Population - Wilkosc, Monika; Markowska, Anita; Zajac-Lamparska, Ludmila; Skibinska, Maria; Szalkowska, Agnieszka; Araszkiewicz, Aleksander (Frontiers in Neural Circuits, 2016)
Brain derived neurotrophic factor is considered to be connected with memory and learning through the processes of long term synaptic potentiation and synaptic plasticity. The aim of the study was to examine the relationship between precursor BDNF (proBNDF) and mature BDNF (mBDNF) serum levels and performance on Rey Auditory-Verbal Learning Test (RAVLT) in 150 healthy volunteers. In addition, we have verified the relationships between serum concentration of both forms of BDNF and RAVLT with sociodemographic and lifestyle factors. We found no strong evidence for the correlation of proBDNF and mBDNF serum levels with performance on RAVLT in healthy Polish population in early and middle adulthood. We observed the mBDNF serum concentration to be higher in women compared with men. Moreover, we revealed higher mBDNF level to be connected with lower Body Mass Index (BMI). In turn, the results of RAVLT correlated with sociodemographic and lifestyle factors, such as: age, education, gender, BMI and smoking.